At the origins of petroleum geology. A review of the book by A.A. Matveychuk “The first petroleum geologists of Russia. Historical sketches” - V. P. Karpov (Известия высших учебных заведений: Геология и разведка)
This book review analyzes historical essays by A.A. Matveychuk about outstanding Russian petroleum geologists. Through the prism of their lives and activities, Matveychuk outlines the first steps in the formation of Russian petroleum geology. Particular attention is paid to the contribution of G.P. Gelmersen, G.V. Abih, and K.I. Bogdanovich, as well as their associates and like-minded people, to the geological study of various Russian regions and to the creation of new organizational structures and scientific schools. It is the activity of the pioneers of petroleum geology that largely determined the shift in the state’s priorities towards oil exploration, which further supported the country’s industrialization in the late 19th—early 20th centuries. The historical events, in which geologists became contemporaries and active participants, were studied. The personalistic approach used by the author in his studies of the initial historical stage of petroleum geology has created a vivid and fairly comprehensive picture of the early history of the industry.